2020
DOI: 10.3398/042.011.0104
|View full text |Cite
|
Sign up to set email alerts
|

Temporospatial Shifts in Sandhill Crane Staging in the Central Platte River Valley in Response to Climatic variation and Habitat Change

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 105 publications
(217 reference statements)
0
21
0
Order By: Relevance
“…Research suggests we are already observing the cumulative effects of wetland habitat loss and climate change on North American crane species. Pearse et al (2018a) demonstrated that the AWBP's migration corridor is shifting east at a rate of 1.2 km/year and research suggests droughts in the southern Great Plains have been a major driver of irregular Whooping Crane and Sandhill Crane wintering distributions in recent years (Wright et al, 2014;Harner et al, 2015;Caven et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests we are already observing the cumulative effects of wetland habitat loss and climate change on North American crane species. Pearse et al (2018a) demonstrated that the AWBP's migration corridor is shifting east at a rate of 1.2 km/year and research suggests droughts in the southern Great Plains have been a major driver of irregular Whooping Crane and Sandhill Crane wintering distributions in recent years (Wright et al, 2014;Harner et al, 2015;Caven et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…As breeding bison populations may grow quickly, grasslands grazed by bison may be prone to overgrazing, trampling, and other negative impacts on birds, rendering grasslands unsuitable for Bobolinks and other species with similar life histories. As identifying and managing for conditions to improve Bobolink productivity are a conservation priority [ 37 ], we recommend that conservation land managers avoid overgrazing grasslands and prioritize protecting birds from disturbance during the nesting season, including by grazing bison or cattle, haying, and burning [ 27 , 118 , 119 , 120 ], to maximize breeding bird abundance and productivity. Favorable grassland management practices for Bobolinks and birds with similar life histories appear to include light, short-duration rotational grazing as well as hay harvesting and patch burning outside the bird breeding season.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Bobolinks and other migratory birds are exhibiting responses to regional climate change, which has resulted in a trend towards warmer temperatures and significantly higher precipitation in our study area and region [ 63 , 64 , 120 , 121 ]. Despite Bobolink abundance and productivity exhibiting positive correlations with wetter and warmer conditions, however, Bobolink populations did not exhibit empirical increases over the time period of our study.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Furthermore, the hydrology of the Platte River has been profoundly altered by damming, diversion (e.g., canals), and groundwater pumping, resulting in large decreases in annual discharge, peak flows, river width, and groundwater levels that maintain riparian wetlands ( Currier 1989 ; Wesche et al., 1994 ; Simons and Associates 2000 ; Henszey et al., 2004 ; Murphy et al., 2006 ; Caven et al., 2019a ). Additionally, the removal of natural and periodic disturbances from the river valley, such as significant flood pulses and wildfires, resulted in large increases in riparian woodland and shrubland landcover manifest as accretion within the former channel bed as well as encroachment into remaining herbaceous habitats ( Williams 1978 ; Currier 1982 ; Caven et al., 2019b ; Fogarty et al., 2020 ). Furthermore, the disappearance of historic grazers and browsers such as Plains Bison ( Bison bison ) and Elk ( Cervus canadensis ), as well as their concurrent replacement by domesticated Cattle ( Bos taurus ), also likely altered patterns of vegetation composition in remaining herbaceous habitats ( Hart 2001 ; Towne et al., 2005 ; Fricke et al., 2008 ; O'Connor et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the disappearance of historic grazers and browsers such as Plains Bison ( Bison bison ) and Elk ( Cervus canadensis ), as well as their concurrent replacement by domesticated Cattle ( Bos taurus ), also likely altered patterns of vegetation composition in remaining herbaceous habitats ( Hart 2001 ; Towne et al., 2005 ; Fricke et al., 2008 ; O'Connor et al., 2020 ). However, beginning in the mid-1970s private conservation organizations began to protect, restore, manage, and study herbaceous habitats in the CPRV for the benefit of migratory birds, particularly the Whooping Crane, as this area was designated “critical habitat” for the species under the Endangered Species Act in 1978 ( USFWS 1978 , Currier et al., 1985 , Pfeiffer 1999 , Vrtiska and Sullivan, 2009 ; Caven et al., 2019b , 2020 ).…”
Section: Introductionmentioning
confidence: 99%